2020
DOI: 10.3390/ijerph17020430
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Driving Behavior Based on Dynamic Changes of Personality States

Abstract: This study investigated the relationship between personality states and driving behavior from a dynamic perspective. A personality baseline was introduced to reflect the driver’s trait level and can be used as a basic reference for the dynamic change of personality states. Three kinds of simulated scenarios triggered by pedestrian crossing the street were established using a virtual reality driving simulator. Fifty licensed drivers completed the driving experiments and filled in the Neuroticism Extraversion Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Allport [26] defined personality traits as the dynamic organization within the individual of those psychophysical systems that determined his unique adjustments to his environment. Personality traits can influence user attitude and behavior [27,28]. Among the related personality traits' papers, the five-factor model has been recognized by most researchers as the most reasonably individual personality model [29].…”
Section: The Influence Of Personality Traits On User Feedbackmentioning
confidence: 99%
“…Allport [26] defined personality traits as the dynamic organization within the individual of those psychophysical systems that determined his unique adjustments to his environment. Personality traits can influence user attitude and behavior [27,28]. Among the related personality traits' papers, the five-factor model has been recognized by most researchers as the most reasonably individual personality model [29].…”
Section: The Influence Of Personality Traits On User Feedbackmentioning
confidence: 99%
“…The user's profile, particularly the personality traits, has also been associated with an effect on driving performance and technology acceptance [44,70,75]. A future study may investigate the association between user personality traits and depression level on the efficacy of the intervention.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The personality factors, such as the Five-Factor Model ( Costa and McCrae, 1992 ), have been used in numerous studies in relation to risky driving. Earlier studies about extraversion ( Lajunen, 2001 ; Parr et al, 2016 ; Braitman and Braitman, 2017 ; Wang et al, 2018 , 2020 ), neuroticism ( Jovanović et al, 2011 ; Wang et al, 2018 ; Soori and Yousefinezhadi, 2020 ) and openness to experience ( Parr et al, 2016 ; Wang et al, 2020 ) have shown that these personality factors often increase the propensity of various types of risky driving (e.g., distracted driving and aggression) while drivers scoring high in agreeableness and consciousness have been reported to commit risky driving less frequently ( Jovanović et al, 2011 ; Wang et al, 2018 , 2020 ; Hussain et al, 2020 ). When evaluating the effects of personality on risky driving, it is important to bear in mind that those relationships depend on the type of risky driving concerned: rule violations, driver aggression and distracted driving are related to specific personality factors or combinations of those factors.…”
Section: Introductionmentioning
confidence: 99%